ANALISIS PERDEBATAN ASPEK KETUHANAN DALAM KAJIAN TEOLOGI ISLAM - Muhammadong; Lukman; Nurmila (Journal of Innovation Research and Knowledge, 2021)
The divinity debate among theologians arose after the death of the Prophet Muhammad and took on his role in providing an understanding of Islam. The Mutakallimins argue that the form of God is perfection since the beginning. This argument was put forward in order to ward off the atheist's assumption that this nature exists by itself without any preconceived reasons. Theologians assume that God's actions are in accordance with his promise to give justice to his creatures. The existence of God's actions is based on his knowledge and iradat in the sense that God is free to carry out his actions without being limited by his creatures so that God's actions contain wisdom for his creatures.